2019
DOI: 10.1039/c8cp06159a
|View full text |Cite
|
Sign up to set email alerts
|

Structural transformations of graphene exposed to nitrogen plasma: quantum chemical molecular dynamics simulations

Abstract: Non-equilbrium quantum chemical molecular dynamics simulations of graphene nitrogenation in plasma reveal the importance of cooperative nitrogen rearrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Some of the motifs have been reported in a recent simulation of N collisions with graphene. 27 These surface species underscore the wide range of bonding the nitrogen can have with the carbon surface. The ultimate fate of these species was not explored in the current study because of the long simulation time required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the motifs have been reported in a recent simulation of N collisions with graphene. 27 These surface species underscore the wide range of bonding the nitrogen can have with the carbon surface. The ultimate fate of these species was not explored in the current study because of the long simulation time required.…”
Section: Discussionmentioning
confidence: 99%
“…PLEASE CITE THIS ARTICLE AS DOI:10.1063/5.0028253 a graphene surface. 27 In our calculations, the third-order correction 31,32 was utilized with the 3ob-3-1 Slater-Koster parameter set 33 and the Lennard-Jones (LJ) dispersion model. 34 Because of the semi-empirical nature of the SCC-DFTB method, it is important to assess its accuracy and reliability in describing the systems of our interest.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the DD approach, the energies and forces are computed on the fly, thus avoiding the construction of analytical PESs. This is particularly advantageous for high-dimensional reactive systems, as the development of an analytical PES with multiple reactive channels can be challenging. This DD approach has been successfully used in many chemical dynamics studies, including atom scattering from graphene/graphite surfaces. ,,,,, In our recent publication, this method was applied to the scattering of hyperthermal N­( 4 S) on pristine and modified model graphene surfaces . As in previous studies, , the HOPG surface was modeled as periacene (5 a ,6 z ), as shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Degradation steps can be predicted, but the absorption of these dopants into graphene is not known. Defects and oxygen functionalities are predicted to play a significant role, and certain DFT studies have tried to uncover reaction dynamics on particular carbon defects and oxygen functionalities using ammonia as a source. Although some insight is shown in these studies, DFT studies are limited due to high computational costs. These cannot provide a dynamics of the binding process, and complicated systems like GO cannot be studied.…”
Section: Introductionmentioning
confidence: 99%